Respon Pertumbuhan dan Produksi Tanaman Kembang Kol (Brassica oleracea var. botrytis) Terhadap Pemberian Biochar dan POC Urin Kambing - Calvin, Mirza; Lubis, Najla; Sajar, Suryani (UNIVERSITAS LABUHANBATU, 2025)
One of the ways to increase cauliflower productivity is by providing nutrients for plants through the provision of organic materials. This study used a factorial Randomized Block Design with 2 factors. The design used in this study was a factorial Randomized Block Design with 2 factors. The first factor is Biochar (B) which consists of 4 levels, namely: B0 = 0 kg / polybag, B1 = 100 g / polybag, B2 = 200 g / polybag and B3 = 300 g / polybag. The second factor is goat urine (K) which consists of 4 levels, namely: K0 = 0 ml / liter of water / plot, K1 = 25 ml / liter of water / plot, K2 = 50 ml / liter of water / plot and K3 = 75 ml / liter of water / plot. The parameters observed in this study were plant height, number of leaves, stem diameter, production per sample, production per plot, cauliflower diameter. The results showed that the provision of biochar fertilizer had no significant effect on plant height, number of leaves and stem diameter, but had a very significant effect on production per sample, production per plot and cauliflower diameter. While the provision of goat urine POC had no significant effect on the number of leaves and stem diameter but had a very significant effect on plant height, production per sample, production per plot and cauliflower diameter. The interaction of the two treatments had no significant effect on all observation parameters.Keywords: cauliflower, biochar, goat urine POC